Green University Garden Towards Region Sustainability - Fadeeva, Marina; Cherkasova, Oksana (Universitas Diponegoro, 2021)
Growing actions on putting into practice the policy for improving sustainable development gives universities great variety of opportunities on implementation of different ‘green’ technologies in their campuses. Campus greening is the first step towards sustainability. The purpose of this article is to present existing approaches on the categories of sustainable campus initiatives, their significance for complete region development and the state of the environment. On the example of the inner garden of Volgograd State University, the authors describe the importance of greening the external campus sites for minimization of the negative environmental and health affects for students and faculty staff. The green initiative reflects the institution’s function as center of technological and social regional development. The green garden can reduce stress and also provide an esthetic sense by involving attractive surroundings. The impact of climatic zone on emerging of appropriate management and maintenance systems, meaningful comparison with the past landscape solutions are also reviewed in the present article. By implementing green technologies, the university shows its prudence and readiness to behave responsibly, sensibly and maturely in response to sustainability issues of the present and the future.